Comparison between Kangaroo Mother Care with Standard Care in Preterm Neonate Management (Bangladesh Medical Journal, 2019)
Preterm low birth weight (LBW) babies are unable to control their body temperature and are at greater risk of illness. Kangaroo Mother Care (KMC) is special ways of caring for low birth weight babies. KMC provide thermal care through continuous skin to skin contact, support for exclusive breast feeding and early recognition and response to complication. The aim of the study is to assess thermal control, morbidities feeding pattern of baby getting KMC in comparison to conventional care. The study also give estimation about duration and cost during hospital stay and growth between the babies of two groups. This Randomized Controlled Trial was conducted in the Department of Neonatology, BSMMU, Dhaka from December 2012 to October 2013. Fifty neonate with birth weight 1250 to 1800 gm, gestational age >30 weeks to